Impact of non-pharmaceutical interventions on the COVID-19 epidemic: A modelling study. (December 2020) - Awaidy, Salah Al; Mahomed, Ozayr
Objective: This study aimed to assess the impact of non-pharmaceutical interventions on the COVID-19 epidemic in Oman. Methods: Data were retrieved from published national surveillance data between 24 February and 30 June 2020. To show the impact of the Government introduced public health intervention early in the epidemic, we used a simple disease-transmission model equation of the 2019-n CoV epidemic. Results: From all confirmed cases, the rates of intensive care unit admission were 4.56% (1824). We estimated an R 0 of 3.11 with no intervention would result in nearly the entire population of Oman being infected within 65 days. A reduction of the R 0 to 1.51 provided an estimated 89, 056 confirmed cases, with 167 deaths or 0.4% mortality by June 30 with a requirement of 4052 intensive care unit beds. The current scenario (24 February to 30 June 2020) indicates an R 0 of 1.41, resulting in 40, 070 confirmed COVID-19 cases, 176 deaths and 69% of confirmed cases recovered. Conclusion: In early implementation of non-pharmaceutical interventions, an intensive lockdown has had a profound impact on the mitigation of a large-scale COVID-19 outbreak in Oman.